Effectiveness Of Rom Exercise In Minimizing Delirium In Stroke Patients At Ciamis Hospital - MJW, Endrian; Prasetyo, Teguh; Supriadi, Dedi; Pauji Salam, Wulan Anugrah; Wahyudi, Deni (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: this study aims to determine the effectiveness of ROM in minimizing the occurrence of delirium in stroke patients at Ciamis Hospital. Methods: this study used a cohort study approach with the type of prospective cohort which was carried out for approximately 3 months. Results: the number of stroke patients with delirium obtained by the researchers was 14 people, the results of the Wilcoxon test analysis showed that there was no significant difference in the level of delirium in respondents before and after giving ROM to stroke patients with delirium with a p value of 0.180 > 0.05. Conclusions: the respondent's delirium level before doing ROM on average is hypoactive delirium, the respondent's delirium level after doing ROM is on average hypoactive delirium. and after ROM is done.